Causal Association Between Genetically Predicted Circulating Metabolites and Pressure Ulcers: A Two-Sample Mendelian Randomization Study - Hu X; Zhang Y; Wu Y; Peng M (Journal of Inflammation Research)
Xiaoli Hu,1 Yue Zhang,2 Yuchao Wu,3 Miao Peng4 1Department of Gastroenterology, The Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of China; 2Department of Pain Management, The Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of China; 3Emergency Intensive Care Unit, The Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of China; 4Department of Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of ChinaCorrespondence: Miao Peng, Department of Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, 25 Taiping Street, Jiangyang District, Luzhou, Sichuan, 646000, People’s Republic of China, Tel +86-15181977618, Email threewaterpm@swmu.edu.cnIntroduction: Pressure ulcers (PU) are skin and soft tissue injuries caused by prolonged localized pressure, friction, or shear forces, particularly affecting individuals with limited mobility. Understanding the mechanisms behind PU formation, including the role of metabolites, is crucial for effective prevention.Methods: We conducted a two-sample MR analysis to explore the causal relationship between circulating metabolites and PU. Exposure data included GWAS data for 1400 metabolites, while outcome data were sourced from a Finnish database. We used multiple MR methods (IVW, MR-Egger, WM, Simple mode, Weighted mode) to estimate causal effects and performed sensitivity analyses to assess robustness. Additionally, we validated the effects of key metabolites on PU through animal experiments.Results: A total of 19 metabolites demonstrated significant causal associations with PU (P < 0.01). Among them, 7 metabolites were linked to PU increased risk, the highest ORs was (IVW: OR [95% CI] = 1.3690 [1.0852– 1.7270]; P = 0.0080) for the spermidine to choline ratio. 12 metabolites with positive effects on PU prevention, the homostachydrine levels showing a highest association (IVW: OR [95% CI] = 0.7497 [0.6206– 0.9056]; P = 0.0028). Sensitivity analyses supported these findings and validated the stability of the results. In animal experiments, rats treated with HD-Hom and LR (Spe/Cho) showed the fastest scab shedding and new epithelial tissue formation, with the smallest residual wound area.Conclusion: This study highlights significant causal relationships between circulating metabolites and PU risk. The identification of the spermidine to choline ratio as a risk factor and homostachydrine levels as a protective factor suggests potential metabolic targets for PU prevention and treatment.Keywords: pressure ulcers, metabolites, Mendelian randomization, causal relationship, circulating metabolites